INTEGRASI TEKNOLOGI DALAM ADMINISTRASI PENDIDIKAN:STUDI OBSERVASI DI SEKOLAH MENENGAH - Definka Puan Shalika Abdillah; Nourma Ayu Sulistiyowati; Yusuf Nurrahman; Sutama Sutama; Ahmad Fathoni (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the implementation and impact of technology integration in educational administration at secondary schools, given that digital transformation has become an urgent necessity for improving the quality of educational services in the era of globalization. Through an observational and survey-based approach involving education staff, this study analyzes the application of school management systems, e-learning platforms, and financial management software used in daily operations. The observation results indicate that technology integration significantly enhances school operational efficiency, facilitates communication among stakeholders, accelerates administrative processes, and supports more accurate and transparent data-driven decision-making. Nevertheless, this study also identifies several significant challenges, including limited technological infrastructure, low digital competence among some education staff, access disparities between schools, and resistance to a more digitally oriented work culture. These challenges have the potential to hinder implementation effectiveness if not addressed comprehensively. Based on these findings, this study recommends strengthening continuous training programs, providing adequate and evenly distributed technological infrastructure, and formulating systematic and well-planned technology integration policies as key prerequisites for the success of digital transformation in secondary school educational administration.